2007
DOI: 10.1128/jb.01395-06
|View full text |Cite
|
Sign up to set email alerts
|

The fox Operon from Rhodobacter Strain SW2 Promotes Phototrophic Fe(II) Oxidation in Rhodobacter capsulatus SB1003

Abstract: In this study, we circumvented this problem by taking a heterologous-complementation approach to identify a three-gene operon (the foxEYZ operon) from Rhodobacter sp. strain SW2 that confers enhanced light-dependent Fe(II) oxidation activity when expressed in its genetically tractable relative Rhodobacter capsulatus SB1003. The first gene in this operon, foxE, encodes a c-type cytochrome with no significant similarity to other known proteins. Expression of foxE alone confers significant light-dependent Fe(II) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
86
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 56 publications
(58 reference statements)
2
86
0
Order By: Relevance
“…Neither the Zetaproteobacteria SAGs nor isolates contain homologs to well-characterized genes involved in iron oxidation identified in other microorganisms including iro (Amouric et al, 2011), rus (Cox and Boxer, 1978), mtoAB (Shi et al, 2012), pioABC , foxEYZ (Croal et al, 2007) and cyt579 (Singer et al, 2008). Previous studies have suggested that the Zetaproteobacteria may use a molybdopterin oxidoreductase and alternative respiratory complex III mechanism to carry out iron oxidation (Singer et al, 2011).…”
Section: Potential For Iron Oxidationmentioning
confidence: 99%
“…Neither the Zetaproteobacteria SAGs nor isolates contain homologs to well-characterized genes involved in iron oxidation identified in other microorganisms including iro (Amouric et al, 2011), rus (Cox and Boxer, 1978), mtoAB (Shi et al, 2012), pioABC , foxEYZ (Croal et al, 2007) and cyt579 (Singer et al, 2008). Previous studies have suggested that the Zetaproteobacteria may use a molybdopterin oxidoreductase and alternative respiratory complex III mechanism to carry out iron oxidation (Singer et al, 2011).…”
Section: Potential For Iron Oxidationmentioning
confidence: 99%
“…Another three-gene operon, the fox operon, has been identified in Rhodobacter sp. strain SW2 and shown to confer enhanced phototrophic iron oxidation reactivity upon the genetically tractable strain Rhodobacter capsulatus SB1003 (Croal et al, 2007).…”
Section: Genomic and Molecular Biologymentioning
confidence: 99%
“…In the companion paper to this article, we report the discovery of a c-type cytochrome and a putative pyrroloquinoline quinone-containing enzyme from an Fe(II)-oxidizing strain-Rhodobacter sp. strain SW2-that stimulate Fe(II) oxidation activity in its close relative Rhodobacter capsulatus SB1003 (11). Because our ability to explore the mechanistic basis of Fe(II) oxidation in SW2 is limited because of the impracticality of direct mutational analysis (11), we established a genetic system in a different Fe(II)-oxidizing phototroph, Rhodopseudomonas palustris TIE-1 (28).…”
mentioning
confidence: 99%